Analisis of The Semiotic Meaning of The Poem "Gray Forest in The Forest" by Sapardi Djoko Damono - Yuliana Ana Awa; Enung Nurhayati (JLER (Journal of Language Education Research), 2024)
This research aims to analyze the semiotic meaning of one of Sapardi Djoko Damono's poems entitled "Gray forest in the rain." In this poem there are many meanings or symbols that are difficult for the reader to understand. Therefore, the reader analyzes this poem. The method used in this research is descriptive qualitative. Descriptive qualitative is a method that can describe, analyze, explain, interpret, and reveal the meaning and facts of scientific logic. The stages carried out by researchers in analyzing semiotic meaning are reading and understanding the entire content of the poem. Furthermore, the signs and markers found will be analyzed using Ferdinand De Saussure's theory, because in semiotic studies Ferdinand De Saussure's theory is considered the most important to analyze the signs, symbols, symbols conveyed by the poet in his work. The result of the poem 'Gray forest in the rain' depicts silence, darkness, and deep sadness. Each stanza and line in the poem depicts sadness as if the rain is falling and the forest reveals the real silence in endless sadness. Weeping is always enveloped in all the humming that is said.